Role of Gonadotropin-Releasing Hormone (GnRH) in Ovarian Cancer - Carsten Gründker; Günter Emons (Cells, 2021)
The hypothalamus–pituitary–gonadal (HPG) axis is the endocrine regulation system that controls the woman’s cycle. The gonadotropin-releasing hormone (GnRH) plays the central role. In addition to the gonadotrophic cells of the pituitary, GnRH receptors are expressed in other reproductive organs, such as the ovary and in tumors originating from the ovary. In ovarian cancer, GnRH is involved in the regulation of proliferation and metastasis. The effects on ovarian tumors can be indirect or direct. GnRH acts indirectly via the HPG axis and directly via GnRH receptors on the surface of ovarian cancer cells. In this systematic review, we will give an overview of the role of GnRH in ovarian cancer development, progression and therapy.